Quality Improvement Program for Colocation Data Center Services Using Quality Function Deployment (QFD) - Jiyi Nur Fauzan; Moses Laksono Singgih (Institut Teknologi Sepuluh Nopember, 2020)
When a product is launched, it's always been expected by the company that the product is going to be sold out in the market. But, after three years of selling XYZ colocation data center services, the sales of this product still hasn't achieve its target. Therefore, an evaluation is needed to know how costumers value the product in the market and what's needs to be done to improve its value. XYZ Data Center Management has conducted a preliminary analysis through discussion with customers, a comparative study with competitors, and discussion with internet service provider association. It's concluded that there is quality in XYZ Data Center, both in features and services that don't satisfying enough. Further analysis then conducted with Quality Function Deployment or QFD as a research method. The reason behind the use of QFD is because of its ability to identify what customers want, and translate it into the company's need in terms of technical responses. The result obtained from this research is the attributes that customers need and the technical responses required to answer it. Examples of attributes are the availability of the working room, the availability of site visit procedure, the accuracy of time needed for installation, etc. And for technical response, the examples are making a portal for trouble handle monitoring in integration with a call center, an improvement on IT Hall layout building a portal for installation monitoring, etc.